2020
DOI: 10.29252/mlj.14.3.19
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, identification, and antibacterial susceptibility testing of Moraxella catarrhalis isolated from the respiratory system of patients in northern Iran

Abstract: Background and Objectives: Moraxella catarrhalis is considered as an emerging pathogen and a new nosocomial infection agent. This study was conducted to isolate and identify M. catarrhalis from clinical samples (respiratory tracts) and assess them for antimicrobial susceptibility patterns. Methods: In total, 280 samples were collected from patients with respiratory tract infection, and 120 samples were obtained from healthy individuals in the control group. The isolates were identified by phenotyping and genot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(25 citation statements)
references
References 31 publications
1
24
0
Order By: Relevance
“…A study assessed resistance trends for M. catarrhalis in Twain, showed that all isolates were susceptible to amoxicillin/clavulanate, chloramphenicol, ce xime, cipro oxacin, erythromycin, levo oxacin [19]. Based on our studies all or majority of isolated M. catarrhalis had susceptibility to amoxicillin/clavulanate and erythromycin [10,11,17], and in two of our study study the susebility to cipro oxacin was high [10,17] while in another study 70% of isolated M. catarrhalis had resistancy to cipro oxacin [11]. In another study were conducted in Pakistan, about 45% of the cultures showed resistance to macrolides and 59% showed resistance to quinolones [20], nerveless, in our study majority of isolated M.cattarhalis had susceptibility to macrolides and quinolones.…”
Section: Catarrhalissupporting
confidence: 49%
See 4 more Smart Citations
“…A study assessed resistance trends for M. catarrhalis in Twain, showed that all isolates were susceptible to amoxicillin/clavulanate, chloramphenicol, ce xime, cipro oxacin, erythromycin, levo oxacin [19]. Based on our studies all or majority of isolated M. catarrhalis had susceptibility to amoxicillin/clavulanate and erythromycin [10,11,17], and in two of our study study the susebility to cipro oxacin was high [10,17] while in another study 70% of isolated M. catarrhalis had resistancy to cipro oxacin [11]. In another study were conducted in Pakistan, about 45% of the cultures showed resistance to macrolides and 59% showed resistance to quinolones [20], nerveless, in our study majority of isolated M.cattarhalis had susceptibility to macrolides and quinolones.…”
Section: Catarrhalissupporting
confidence: 49%
“…Penicillin resistance was 100% and 70% in two of our studies [10,11], and even though one of our studies did not refer to the percentage of penicillin resistance, it did show that the majority of microorganisms were penicillin-resistant. [12].…”
Section: Catarrhalismentioning
confidence: 65%
See 3 more Smart Citations